2018
DOI: 10.1038/s41467-018-07093-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the recognition of sulfur in phosphorothioated DNA

Abstract: There have been very few reports on protein domains that specifically recognize sulfur. Here we present the crystal structure of the sulfur-binding domain (SBD) from the DNA phosphorothioation (PT)-dependent restriction endonuclease ScoMcrA. SBD contains a hydrophobic surface cavity that is formed by the aromatic ring of Y164, the pyrolidine ring of P165, and the non-polar side chains of four other residues that serve as lid, base, and wall of the cavity. The SBD and PT-DNA undergo conformational changes upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 60 publications
0
48
0
Order By: Relevance
“…ScoMcrA was named by analogy to EcoKMcrA, to highlight the shared endonuclease domains and the endonuclease activity against 5mC-modified DNA (Liu et al, 2010). However, the domain structures of EcoKMcrA and ScoMcrA are clearly different (Liu et al, 2018). EcoKMcrA consists of an N-terminal 5hmC binding domain, termed NEco, and an HNH catalytic domain.…”
Section: Sbd-sra-hnh Endonuclease Scomcramentioning
confidence: 99%
See 1 more Smart Citation
“…ScoMcrA was named by analogy to EcoKMcrA, to highlight the shared endonuclease domains and the endonuclease activity against 5mC-modified DNA (Liu et al, 2010). However, the domain structures of EcoKMcrA and ScoMcrA are clearly different (Liu et al, 2018). EcoKMcrA consists of an N-terminal 5hmC binding domain, termed NEco, and an HNH catalytic domain.…”
Section: Sbd-sra-hnh Endonuclease Scomcramentioning
confidence: 99%
“…Sulfur binding domains (SBDs) are widespread in prokaryotic DNA binding proteins (Liu et al, 2018), but have so far not been found in eukaryotes. As the name indicates, they have a preference for sulfur in the Rp configuration in the DNA backbone.…”
Section: Introductionmentioning
confidence: 99%
“…This role can be inferred from the comparison with the SRA domain, which shares the PUA-like fold with EVE. The SRA domain has been characterized in considerable detail, including the base-flipping 5mC DNA-binding mechanism and characterization of its function as a modified DNA specificity module in Type IV REs which restrict DNA containing 5mC, 5hmC, and glucosylated 5hmC (Arita et al 2008;Avvakumov et al 2008;Hashimoto et al 2008;Liu et al 2018;Weigele and Raleigh 2016). Therefore, EVE domains deployed in modification-dependent restriction likely use a base-flipping mechanism, similar to that of SRA, to sense modified cytosine in various sequence contexts although some might bind derivatives of the other pyrimidine bases, thymine or uracil, which are hypermodified in some phage genomes (Weigele and Raleigh 2016).…”
Section: Eve As a Specificity Domain In Modification-dependent Restrimentioning
confidence: 99%
“…Quantitative studies of DNA phosphorothioate modifications in prokaryotic genomes demonstrate that DNA phosphorothioate modification is widely distributed in diverse sequence contexts in bacteria and archaea [5]. The sulfur atom in R pphosphorothioated dsDNA points to the major groove of dsDNA, facilitating its identification by the sulfur-binding domain of ScoMcrA, as well as its correct cleavage, so that bacteria cannot spread and survive in other hosts [11,12]. The R p -phosphorothioated DNA functions as an antioxidant, protecting the hosting bacteria against peroxide when they live with oxidants [10].…”
mentioning
confidence: 99%
“…The sulfur atom in R pphosphorothioated dsDNA points to the major groove of dsDNA, facilitating its identification by the sulfur-binding domain of ScoMcrA, as well as its Abbreviations dnd, DNA degradation; DndE A7K , DndE variant A7K; DndE G21/24K , DndE G21/24K variant; DndE L58F and DndE L58E , DndE variants L58F and L58E; DndE WT , wild-type DndE; FP, fluorescence polarization; HTH, helix-turn-helix; K d , dissociation constants; SSRF, Shanghai Synchrotron Radiation Facility. correct cleavage, so that bacteria cannot spread and survive in other hosts [11,12].…”
mentioning
confidence: 99%